2011
DOI: 10.1159/000326802
|View full text |Cite
|
Sign up to set email alerts
|

Different Effect of IgA Nephropathy and Polycystic Kidney Disease on Arterial Stiffness

Abstract: Background: Renal function is a major predictor of vascular function and cardiovascular diseases. Little information exists about the effect of specific renal diseases on vascular function in chronic kidney diseases (CKD). Methods: One hundred and twenty patients (60 with IgA nephropathy, IgAN, and 60 with polycystic kidney disease, PKD) with CKD stages 1–4 were studied and compared. Pulse-wave velocity was measured by the digital volume pulse (DVP) method and stiffness index (SIDVP) was derived. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 96 publications
(52 reference statements)
2
16
0
Order By: Relevance
“…The present study provides primary data on the association between the etiology of ESRD and cfPWV among HD patients, where vascular renal disease and diabetic nephropathy were independently associated with higher cfPWV as compared with other etiologies of ESRD. Prior studies have demonstrated that a history of either hypertension or diabetes mellitus is associated with increased arterial stiffness among HD patients [13, 14], but investigations that address the association between the renal sequelae of both diseases and arterial stiffness in this population are scarce [15, 16]. The current results suggest that development of renal disease due to either chronic hypertension (vascular renal disease) or diabetes (diabetic nephropathy) is more strongly associated with arterial stiffness than either disease alone, demonstrating the direct role of the kidneys on arterial stiffness that extends beyond the risks attributed to hypertension and diabetes alone.…”
Section: Discussionmentioning
confidence: 99%
“…The present study provides primary data on the association between the etiology of ESRD and cfPWV among HD patients, where vascular renal disease and diabetic nephropathy were independently associated with higher cfPWV as compared with other etiologies of ESRD. Prior studies have demonstrated that a history of either hypertension or diabetes mellitus is associated with increased arterial stiffness among HD patients [13, 14], but investigations that address the association between the renal sequelae of both diseases and arterial stiffness in this population are scarce [15, 16]. The current results suggest that development of renal disease due to either chronic hypertension (vascular renal disease) or diabetes (diabetic nephropathy) is more strongly associated with arterial stiffness than either disease alone, demonstrating the direct role of the kidneys on arterial stiffness that extends beyond the risks attributed to hypertension and diabetes alone.…”
Section: Discussionmentioning
confidence: 99%
“…They proposed this finding to result from endothelial dysfunction mediated by impaired nitric oxide synthesis and have followed-up this hypothesis by demonstrating endothelial dysfunction in vitro together with impaired acetylcholine mediated the vasodilatation of the small subcutaneous resistance arteries in a group of young normotensive ADPKD patients [23]. In another study [24], arterial stiffness more pronounced in ADPKD than in IgA nephropathy patients. Likewise, Menon et al [25] have demonstrated that inflammation is evident in the circulation early in ADPKD, even when kidney function is preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Increased arterial stiffness and ADPKD ADPKD patients exhibit vascular dysfunction as increased arterial stiffness and this stiffness is evident very early in the course of ADPKD even in patients with normal renal function (5,40). In a previous cross-sectional study, we showed that arterial stiffness is increased as the renal function declined in a homogeneous group of CKD patients with IgAN (22). Moreover, we concluded that the etiology of CKD may also affect the degree of arterial stiffness by comparing IgAN and ADPKD patients, as our findings have shown that arterial stiffness develops earlier and the progression is more rapid in ADPKD than in IgAN patients with comparable renal function (22).…”
Section: Increased Arterial Stiffness In Ckdmentioning
confidence: 83%
“…We used the finger photoplethysmography method by the Pulse Trace System (Micro Medical Ltd., Rochester, UK) to assess pulse wave velocity (PWV) as described earlier (21,22). This method allows the determination of the stiffness index (SI), which can be derived from the digital volume pulse (DVP), and is reflected as SI DVP .…”
Section: Determination Of Vascular Stiffnessmentioning
confidence: 99%